Feedback Linearization Synchronization of Unified Chaotic Systems - Chen, Chang-Zhong; Fan, Tao; Wang, Bang-Rong; Nik, Hassan Saberi; He, Ping (Journal of Applied Nonlinear Dynamics, 2026)
The goal of this paper is to present a method that can be used to synchronize unified chaotic systems. The method is mainly based on the technology of feedback Linearization of nonlinear control systems. Numerical simulations are then provided to show the effectiveness and feasibility of the proposed chaos control and synchronization schemes.